Samambaias e licófitas das serras ferruginosas da Floresta Nacional de Carajás, Pará, Brasil - Andre Jardim Arruda (2014)
The Serras dos Carajás is a complex of ferruginous highlands located in the southeast region of the Brazilian State of Pará, and are almost completely placed within the National Forest (FLONA) of Carajás, including the municipalities of Parauapebas, Canaã dos Carajás and Água Azul do Norte. Those highlands are one of the largest iron districts of Brazil. Their altitudes range from 250 m, at the foothills, to 700-800 m at the flat tops, which stands out from the surrounding tropical forest by the predominantly savanna and grassland vegetations. The current study aimed at surveying the pteridophyte community of four ferruginous highlands of the Carajás complex: Serra Sul, Serra do Tarzan, Serra Norte and Serra da Bocaina. The study was all based on material lodged at the herbarium of the Federal University of Minas Gerais (BHCB), totaling 1068 specimens studied collected between 2007 and 2013 and identified based on specific literature and by comparisons with previously identified samples. In total, 181 species of pteridophytes have been identified (13 lycophytes and 168 ferns). The lycophytes are divided into three families: Isoetaceae (Isoetes), Lycopodiaceae (Phlegmariurus and Palhinhaea) and Selaginellaceae (Selaginella), which was the most representative, with nine species. The two species of Isoetes are new to science and are in the process of description. The ferns are distributed into 21 families and 59 genera, and the most representative families were: Pteridaceae (36 species), Dryopteridaceae (19), Thelypteridaceae (18), Hymenophyllaceae (15), Aspleniaceae (11) Blechnaceae (9), Lomariopsidaceae and Tectariaceae (8 each), and Cyatheaceae (5), totaling 72% of fern species. The genera with the highest number of species were: Adiantum and Thelypteris (17 each), Asplenium (11), Blechnum (9), Trichomanes (8), Cyathea, Nephrolepis and Campyloneurum (5 each), and Elaphoglossum, Microgramma, Pteris, Triplophyllum and Tectaria (4 each), corresponding to 58% of the fern species. Most species are restricted to forest formations and 124 (69%) are widely distributed across the Neotropics . Of the remaining species, 28 (16%) are South-American, 12 (7%) Pantropical, and nine endemic to Brazil (5%). Highlights include 22 new records, three for Brazil and 19 for the State of Pará. Four species are endemic to the Carajás region: Blechnum areolatum B. longipilosum, Isoetes sp. 1 and Isoetes sp. 2.; and one specie is endemic to Pará State: Thelypteris indusiata. The number of species found represents 58% of the total number of pteridophyte species known for Pará State and 33% of that known for Brazilian Amazon. Detailed taxonomic identification keys and genus/species diagnose are provided, together with comments, description of the environment for each collection site, geographic distribution, description of the sampled material and list of occurring species in the study site.